Exploring a Consumption Value Model for Islamic Halal Cosmetics - Ana Toni Roby Candra Yudha; Rizka Rahmatillah Zidna; Novi Febriyanti (Faculty of Economic and Business, 2024)
Research Originality: Halal cosmetics segmentation requires detailed analysis to enable stakeholders from the industry sector to optimize marketing and sales. The findings of this study are interesting, the market opportunity specifically for women is not only in consumption volume but also production, especially with market segmentation among millennials and Gen Z.Research Objectives: This research aims to determine the simultaneous and partial effects of halal labeling, product quality, religiosity, and online consumer reviews on purchasing decisions regarding halal cosmetic products among female and male consumersResearch Methods: This research employed an online survey method with 203 respondents. It also employed the SEM-PLS to evaluate models and validate hypotheses, and Multi-Group Analysis (MGA), which is employed to determine the gender effect's position on the hypotheses.Empirical Results: The results with the SEM-PLS method show that product quality, online consumer reviews, and religiosity satisfactorily influence purchasing decisions, this is not the case with the halal label. It seems that online consumer reviews are more suitable for male consumers. Appearance and persuasive factors are more important for male consumers who value rational factors compared to female consumers.Implications: The findings of this research are significant due to the comparison drawn between male and female consumers. Such a comparison aids practitioners and business professionals in effectively delineating market demands and preferences. When developing halal cosmetic products, manufacturers must consider not only the product's sales potential but also its efficacy and potential side effects upon usage.JEL Classification: M5, M10, M21How to Cite:Yudha, A.T.R.C., Zidna, R.R & Febriyanti, N. (2024). Exploring a Consumption Value Model for Halal Cosmetics. Etikonomi, 23(2), 465 – 480. https://doi.org/10.15408/etk.v23i2.36080.